Investigation of Total Phenol Content in Red Pomegranate Leaves Extract (Punica granatum L.) - Januarista, Terra; Mubarakati, Nurul Jadid; Ramadhan, Majida (JSMARTech, 2024)
Red pomegranate leaves (Punica granatum L.) is one of the plants that has many benefits and potential as herbal medicine. Red pomegranate leaves have bioactivities such as alkaloids, flavonoids, phenols, saponins, tannins and terpenoids so that they can be used as an alternative antioxidant. This study aims to determine the comparison of the amount of total phenol content in red pomegranate leaves extract using maceration and digestion extraction methods. Total phenol content was determined using the Folin Ciocalteau method with a spectrophotometer UV-Vis. The research method carried out was descriptive experimental quantitative and data analysis was carried out using one way ANOVA. The results of the determination of total phenol content in gallic acid obtained a regression equation y = 0.012x + 0.545 with R2 = 0.9981. The results showed that the total phenol content in the ethanol extract of red pomegranate leaves was greater with the maceration method of 91.83 (µg GAE/g sample) compared to the digestion method of 83.27 (µg GAE/g sample). It can be concluded that the two methods used on red pomegranate leaf samples have no significant difference in total phenol content.